1999
DOI: 10.1016/s0194-5998(99)70055-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety of home‐based and office allergy immunotherapy: A multicenter prospective study

Abstract: During a 1-year period, 27 otolaryngic allergy practices recorded all systemic reactions to immunotherapy resulting from 635,600 patient visits and 1,144,000 injections. Sixty percent of injections were given at home. Major systemic reactions were observed after 0. 005% of injections. There were no hospitalizations or deaths. Eighty-seven percent of major reactions began within 20 minutes of injection. Frequently observed risk factors for major reactions were buildup phase of immunotherapy, active asthma, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
3
28
0
1
Order By: Relevance
“…Además la inmunoterapia domiciliaria es más segura y produce menos reacciones adversas graves (9). Se observó una reducción drástica de la toxicidad, además de confirmar la eficacia de la combinación terapéutica subcutánea a bajas dosis (8) e incluso la remisión del tumor a largo plazo (7).…”
Section: Resultsunclassified
“…Además la inmunoterapia domiciliaria es más segura y produce menos reacciones adversas graves (9). Se observó una reducción drástica de la toxicidad, además de confirmar la eficacia de la combinación terapéutica subcutánea a bajas dosis (8) e incluso la remisión del tumor a largo plazo (7).…”
Section: Resultsunclassified
“…12 Consistent with these results, several other reports have previously documented the safety of self-administered or home-based SCIT. 1317 The authors concluded that the low systemic reaction rates reported showed that home-based immunotherapy was safe. 1317 …”
Section: Discussionmentioning
confidence: 99%
“…1317 The authors concluded that the low systemic reaction rates reported showed that home-based immunotherapy was safe. 1317 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single intradermal tests not paired with SPT are very sensitive but have a greater potential to cause significant adverse reactions 31 . IDT was evaluated through a prospective, multicenter study that showed that serious reactions are uncommon 32 . This technique and its related immunotherapy have not been shown to have a higher risk of serious local or systemic reaction when comparing IDT with SPT 15 .…”
Section: Introductionmentioning
confidence: 99%